Network disruption detected in NI (Nicaragua) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Nicaragua. Data sourced from IODA.
Network Disruption Incident ID: NI-2026-0002. Severity: critical. Confidence: 65%